Food-derived extracellular vesicles for treatment of osteoporosis: a systematic review and meta-analysis of preclinical animal studies - Hongchen Shi; Ying Zhang; Qingsong Zhu; Yuntong Lian; Weiqiang Geng (European Journal of Medical Research)
Abstract Objective Food-derived extracellular vesicles (EVs) are considered a novel therapeutic approach for osteoporosis. However, their efficacy in treating osteoporosis remains unclear. This systematic review and meta-analysis aim to preliminarily evaluate and explore the effects of food-derived EVs in animal models of osteoporosis. Methods PubMed, Embase, and Web of Science databases were searched for preclinical studies on food-derived EVs in the treatment of osteoporosis, up to November 25, 2024. A meta-analysis was conducted to evaluate the effects of food-derived EVs on bone mineral density (BMD), bone volume/total volume (BV/TV), trabecular thickness (Tb.Th), trabecular separation/marrow thickness (Tb.Sp), trabecular number (Tb.N), and serum bone turnover markers in osteoporosis animal models. Results Six studies met the inclusion criteria for the meta-analysis. The results showed that food-derived EVs contributed to increases in BMD and bone mass markers (BV/TV, Tb.Th, and Tb.N), while promoting the expression of bone formation markers (OPG and PINP) and reducing the expression of bone resorption markers (TRACP 5b and β-CTX). Sensitivity analysis demonstrated the stability of the pooled effect sizes. Conclusions The present meta-analysis suggested that food-derived EVs could improve BMD and bone mass in animal models of osteoporosis. This positive effect may be attributed to the promotion of bone formation mediated by the upregulation of osteogenic markers and the inhibition of bone resorption mediated by the downregulation of osteoclastic markers. Moreover, it is necessary to conduct studies with larger sample sizes and using other animal models to provide important insights for clinical trials.